2020
DOI: 10.1177/0037549720930084
|View full text |Cite
|
Sign up to set email alerts
|

Epistemological aspects of computational simulations and their approach through educational simulations in high school

Abstract: Computer simulations are currently used in diverse scientific disciplines as well as in science teaching. The simulations proposed for physics teaching are designed for specific purposes and allow studying natural phenomena through exploration and/or modeling. In this work, we present an analysis that, based on the theoretical frame provided by the nature of science (NOS), considers some aspects of present discussions on computer simulations that should be taken into account to promote scientifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Students' conceptual and procedural understanding was enhanced as CSs engaged students through the interactive visual environment in which students had opportunities to interact and actively manipulate the experimental settings. Students manipulated the parameters and used the results of the manipulation to construct new meanings constructively (Couch, 2014;Seoane et al, 2022;Wieman et al, 2010). In addition, this study demonstrated that through the use of CSs, male students improved more in their conceptual understanding than female students.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Students' conceptual and procedural understanding was enhanced as CSs engaged students through the interactive visual environment in which students had opportunities to interact and actively manipulate the experimental settings. Students manipulated the parameters and used the results of the manipulation to construct new meanings constructively (Couch, 2014;Seoane et al, 2022;Wieman et al, 2010). In addition, this study demonstrated that through the use of CSs, male students improved more in their conceptual understanding than female students.…”
Section: Discussionmentioning
confidence: 87%
“…Visualization tools, such as computer simulations (CSs), if used in instruction, are likely to facilitate students' understanding and enable them to create or draw their representations (Abdulrahaman et al, 2020;Ariano et al, 2023;Coelho, 2018). Seoane et al (2022) defined CSs as a demonstration of the dynamic behavior of a system according to an approximate mathematical model that is transformed into discrete algorithms to be implemented on a computer. According to Candido et al (2022) and Zacharia and Anderson (2003), using CSs as part of an instructional technique to teach physics' abstract concepts can provide students with the academic tools they need to comprehend these concepts more thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 This section presents a more detailed review of these areas and a hybrid model incorporating both modeling approaches. Relevant work to our study is discussed by Seoane et al 36 The authors have analyzed the relationship between simulation and experimentation and the validity of knowledge generated from the performed simulations. Another work, conducted by Liu and Ma, 37 further discusses a different aspect of cooperation.…”
Section: Introductionmentioning
confidence: 99%